Transthoracic lung ultrasonography in pulmonary alveolar proteinosis – case report - Porzezińska, Maria; Buda, Natalia; Osowicka, Magdalena; Kosiak, Wojciech; Rzepko, Robert; Radzikowska, Elżbieta; Słomiński, Jan Marek; Jassem, Ewa (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
A pulmonary alveolar proteinosis (PAP) is a rare disease characterized by an accumulation of surfactant components in lung alveoli. In diagnosis and monitoring of the disease high resolution computed tomography (HRCT) is usually used. Unfortunately, repeated exposure to CT scanning may be associated with an increased risk of radiation. We present a patient in whom repeated transthoracic lung ultrasonography (TLUS) brought parallel to HRCT data in assessing PAP extent. It may indicate that TLUS might be potentially a relevant tool in monitoring of PAP.